EVALUATION OF THE ANTI-ARTHRITIC ACTIVITY OF THE HYDROETHANOLIC LEAF EXTRACT OF ALCHORNEA CORDIFOLIA IN RATS - Adewale, Adeneye Adejuwon; Ibrahim, Oreagba Adekunle; Ogunbode, Ishola Ismail; Adeola, Kalejaiye Hassanat (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Different decoctions of Alchornea cordifolia leaves are used by Yoruba herbalists (Southwest Nigeria) for the local treatment of ulcers, rheumatic pains, febrile convulsions, and for enhancing physical performance. Materials and methods: In this study, the anti-arthritic effect of 100 – 400 mg/kg/day of the hydroethanolic leaf extract of Alchornea cordifolia (HEAC) was investigated in Complete Freund’s Adjuvant (CFA)-induced arthritic rats as a way of evaluating its efficacy in the local management of arthritis. In addition, the effects of HEAC on liver and renal function parameters as well as its effect on the antioxidant enzyme system were investigated. Arthritis was induced using 0.1 ml of 10 mg/ml of Complete Freund’s Adjuvant (CFA) following 1 h oral pretreatment and 8th day post-arthritic induction with 100, 200 and 400 mg/kg/day of HEAC and 3 mg/kg/day of celecoxib as the reference drug. The anti-arthritic activity of HEAC was assessed based on the ability of HEAC to alter the paw edema diameter, body weight, full blood count, renal and liver function markers, glycoprotein, lysosomal enzymes and possible antioxidant potential in the arthritic rats. Results: Oral pretreatment with 100, 200, and 400 mg/kg/day of HEAC produced significant (p<0.001, p<0.05 and p<0.01) reductions in the paw edema diameter in a non-dose dependent fashion in ACF-induced arthritic rats with the 100 mg/kg/day of HEAC producing the most significant anti-arthritic effect. Similarly, HEAC increased hepatic GSH levels, CAT and SOD activities suggesting possible antioxidant mechanism for its anti-arthritic effect. Conclusion: Overall, results of this study lend credence to the folkloric use of water decoction of Alchornea cordifolia leaves against rheumatoid arthritis. However, further pharmacological investigations would be required at isolating and determining the active anti-arthritic molecule(s) in HEAC in the nearest future.